Peculiarities of legal regulation of certain types of non-contractual obligations in private international law - Rudenko, Oksana (INTERNATIONAL SCIENTIFIC CONFERENCE ”Ethical and Social Dimensions in Public Administration & Law – 7th edition”., 2022)
The article reveals the certain types of non-contractual obligations in private international law. The issue of refusal to use the general collision binding of the place of harm (lex loci delicti commissi) is being studied. Nowadays, instead of that collision binding, which was originally used for each type of non-contractual obligation, several alternative collision bindings are used. In addition to the law of the place where the tort was committed, the article also reveals the features of using such collision bindings as the citizenship of the parties or the place of residence of the parties of the legal relationship, the place of release of the goods, the place of registration of the vehicle, etc.
Keywords: of non-contractual obligations, private international law, lex loci delicti commissi